Value, Satisfaction, Customer Trust and Experience-Based Marketing of Blibli Customers in Bandung - Fariz Pramadani; Sucherly Sucherly; Rita Komaladewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to examine how customer value and experiential marketing can influence customer trust directly and through customer satisfaction. This study focuses on Blibli customers in Bandung City, the sample size in this study is 210 respondents. The data analysis techniques was carried out using the Structured Equation Model (SEM-PLS) using the SmartPLS 3.0 program with measurements of outer model: convergent validity, discriminant validity, composite reliability, and measurements of the inner model; Coefficient Determinant of (R2), Significance (t-value). The results of the study show that customer value has a direct effect on customer satisfaction, experiential marketing has a direct effect on customer satisfaction, customer value has a direct effect on customer trust, experiential marketing has a direct effect on customer trust, customer satisfaction has a direct effect on customer trust, customer value has an effect on customer trust through customer satisfaction and experiential marketing have an effect on customer trust through customer satisfaction, the conclusion is that customer value and experiential marketing have an effect on customer satisfaction so that Blibli's customer trust in the city of Bandung can increase.